2018
DOI: 10.3892/mmr.2018.9139
|View full text |Cite
|
Sign up to set email alerts
|

A three‑lncRNA signature for prognosis prediction of acute myeloid leukemia in patients

Abstract: Long non-coding RNAs (lncRNAs) are transcripts characterized by >200 nucleotides, without validated protein production. Previous studies have demonstrated that certain lncRNAs have a critical role in the initiation and development of acute myeloid leukemia (AML). In the present study, the subtype-specific lncRNAs in AML was identified. Following the exclusion of the subtype-specific lncRNAs, the prognostic value of lncRNAs was investigated and a three-lncRNA expression-based risk score [long intergenic non-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…There was no disease information at all available in Open Targets for the top gene, SNHG29. However, under the alias LRRC75A-AS1 this gene is part of a three-lncRNA signature that has been identified for the prognosis prediction of acute myeloid leukemia (AML) patients 24 . The four other genes had some reported association with leukemia.…”
Section: Resultsmentioning
confidence: 99%
“…There was no disease information at all available in Open Targets for the top gene, SNHG29. However, under the alias LRRC75A-AS1 this gene is part of a three-lncRNA signature that has been identified for the prognosis prediction of acute myeloid leukemia (AML) patients 24 . The four other genes had some reported association with leukemia.…”
Section: Resultsmentioning
confidence: 99%
“…All available RNA-sequencing data of AML samples were searched using The Cancer Genome Atlas (TCGA) database (https://cancergenome.nih.gov/) on March 17, 2018. In total, 187 AML samples with RNA-sequencing data were obtained from TCGA (16,17). According to the age information of the samples, 111 samples from patients under the age of 14 years were included.…”
Section: Methodsmentioning
confidence: 99%
“…Transfection lncRNA LOC285758 overexpression vector (LOC285758; lnc6180620115353-1-5), negative control (NC; lnc6N0000 002-1-10), miR-204-5p mimics (Mimic; miR10022693- [1][2][3][4][5] and Mimic control (miR01102-1-1) were purchased from RIBOBIO (Guangzhou, China). RNase-free H 2 O (ST876; Beyotime, Shanghai, China) was used to dilute LOC285758, NC, Mimic and Mimic control to 20 lM and was stored at À20°C for later use.…”
Section: Blood Samplesmentioning
confidence: 99%
“…Our findings suggest that targeting of miR-204-5p by LOC285758 promotes the cell viability and invasion of AML cells, and thus LOC285758 may have potential as a therapeutic target for AML treatment.Acute myeloid leukemia (AML) is the second most common type of leukemia worldwide [1,2]. The latest statistics revealed that the cure rate of AML in the young is 35%, whereas in the aged it is 15% by modern treatment strategies [3]. AML, which is a highly heterogeneous hematopoietic malignancy with an annual incidence of approximately 3/100 000, remains a great challenge in clinical oncology [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation